Fracture Behavior of Ice in Charpy Impact Testing - Itagaki,Kazuhiko; Sabourin,Richard L (1980)
Specimens prepared from various types of ice without introducing excessive defects were tested at temperatures ranging from -2 to -190 C. These tests indicated slightly higher Charpy values at lower temperatures and in more highly dispersed material concentrations. Three modes of fracture occurred during testing. Depending on the temperature and the material composition, either of the first two modes, normal fracture or multiple fracture, will appear and will show a normal frequency distribution of Charpy values in each type of ice. The third mode, fracture from both ends, which frequently occurred in the NH4F doped ice, gave Charpy values two to five times higher than the mean value for normal fracture. It can, therefore, be concluded that certain types of doping can alter the mode of fracture, through which drastic modifications of impact resistance may be possible. (Author)